Computer-Based Applications for Quality Management Process in Shipbuilding - Renny Rahmadi P; Triwilaswandio W.P.; M. Sholikhan Arif (Institut Teknologi Sepuluh Nopember, 2017)
Abstract¾ In a Shipyard, Quality Management has not been executed systematicaly. Management of inspections are not supported by system which can help Shipyard, Owner Surveyor, Class and State Regulator to control, to search, to review, to evaluate and to do the inspections. This research has a main goal to design a Computer-based Application that makes Quality Management process in Shipbuilding better. Firstly, the Existing Quality management in shipyard was observed which is taken as the sample is PT. PAL Indonesia Shipyard. Secondly, Determining parameters are required in Quality Management Application. Thirdly, Designing Computer-based Applications based on application parameters. Application parameters are identified during shipbuilding stages, processes, outfittings and ship documents, as well as standards and check lists. Software used to design the application is combination of PHP as programming language, Sublime Text 2 as text editor and MySQL as database. This computer-based applications can help quality management implementation in controlling, searching, reviewing, evaluating, and doing the inspection. Once the application has been designed, it was tested by verification and comparison systems. It is concluded that the application system is better than the existing system which is personally conducted in the Shipyard.